HELLP syndrome, A real general disease that threatens the maternal morbidity and mortality at the EHU in Oran - Setti Aouicha Zelmat; NBelhachemie; D Bouabida K Kerbouia; E Boucherit; F Mazour (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Hellp Syndrome (hemolysis, elevatedliver enzymes, lowplatelet count) is an obstetric emergency. It is a form of severity of preeclampsia, itsdiagnosisisdifficultbecause the biologicalpictureisoftenincomplete and rough [1-6]. Several classifications have emerged, the best knownisthat of MISSISSIPI. [7-10], defined by: